PELESTARIAN UNIT PELAKSANA TEKNIS DINAS (UPTD) MUSEUM SUBAK SEBAGAI DAYA TARIK WISATA BUDAYA DI KABUPATEN TABANAN - I Gusti Ayu Arya Ariningsih; Saptono Nugroho (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2015)
ABSTRACT Unit Pelaksana Teknis Dinas (UPTD) Subak Museum is a museum of agricultural equipment storages, it is located in Tabanan regency. The existence of this museum it is important to remember at this time of our generation are less concerned with the existence of paddy which is the spearhead of human life at the same time has become a culture that is ingrained. It is important to preserve Subak Museum for information and education as well as of course to save a variety of objects related of subak. That assumption is underlying me to choose this topic for research. The topic is